Respon Nelayan Terhadap Fenomena Iklim (Perspektif Sosial Ekonomi) - Wahyudi Wahyudi; Muslihin Muslihin; Mauliana Wayudi; Aisyah A Rahman; Muhammad Rizal; Rahmi Rahmi (Departement of Mathematics Education, 2023)
Against the background of climate phenomena, people who rely on fishing are greatly affected by climate change. This phenomenon occurs due to global warming which causes the earth's temperature to continue to increase, thus affecting a prolonged dry season. This phenomenon is known as climate change. Alue Bi Pusong Village, which is located on the coast of Jangka District, Bireuen Regency, is a fishing community. As coastal communities, fishermen rely on the sea as a resource to supply various needs. This problem raises a study question,